Incorporating Yttrium-90 trans-arterial radioembolization (TARE) in the treatment of metastatic pancreatic adenocarcioma: a single center experience. Issue 1 (December 2016) - Kim, Alexander; Unger, Keith; Wang, Hongkun; Pishvaian, Michael
Abstract Background The purpose of this retrospective study was to evaluate the efficacy of incorporating trans-arterial radioembolization (TARE) with systemic chemotherapy in the treatment of liver-dominant metastatic pancreatic ductal adenocarcinoma, with the aim of destroying liver metastases and improving patient outcomes. Methods We retrospectively evaluated 16 patients with liver-dominant metastatic pancreatic ductal adenocarcinoma who underwent TARE between February 2012 and August 2015; 15 of these patients also underwent concurrent systemic chemotherapy. Patient outcomes were assessed using Response Evaluation Criteria In Solid Tumors (RECIST), Version 1.1 and included disease response, median overall survival from the time of diagnosis of metastatic disease, and median overall survival following receipt of TARE. Treatment-related adverse events were assessed using Common Terminology Criteria for Adverse Events (CTCAE), Version 4.03. Results The median overall survival from the time of diagnosis of metastatic disease and following receipt of TARE was 22.0 and 12.5 months, respectively. Overall and liver specific disease response were assessed for 13 patients with follow-up imaging available at the time of study (range 2–13 weeks post TARE). Four patients (31 %) demonstrated partial response and five patients (38 %) had stable disease in the liver at follow-up. One patient developed grade 3 elevation of total bilirubin three months post-treatment and another patient developed radiation cholecystitis directly following TARE. No treatment-related grade 4 or 5 toxicities were seen. Conclusion TARE can be safely combined with systemic chemotherapy for the treatment of liver-dominant metastatic pancreatic cancer. Patient outcomes following this treatment strategy are promising but prospective evaluations are needed to validate these preliminary findings.